Synthesis and Photoluminescent Property of \(\text{MgO:Cr}^{3+}\) Powders - Loan, Trinh Thi; Long, Nguyen Ngoc; Cuong, Le Hung (Communications in Physics, 2012)
MgO:Cr3+ powders with different dopant contents have been synthesized by sol-gel method using the following precursors: magnesium nitrate (Mg(NO3)2), chrome nitrate (Cr(NO\(_3\))\(_3\)), and citric acid. The effect of the Cr\(^{3+}\) concentration and heat-treating temperature on structural and optical properties of the synthesized samples has been studied. For the samples with the low Cr3+-dopant concentrations or low heat-treating temperature, the photoluminescent (PL) spectra consist of sharp lines assigned to the \(^2\)E \(→\) \(^4\)A\(_2\) transition of ions Cr3+ in perfect octahedral symmetry sites. But for the samples with the high Cr\(^{3+}\)-dopant concentrations and undergone high heat-treating temperature, the PL spectra appear a broad emission bands, which is assigned to the \(^4\)T\(_1→ ^4\)A\(_2\) transitions within the Cr\(^{3+}\) ions in the MgO orthorhombic symmetry crystal field.